Integrated use of phosphorus and growth stimulant (actibion) improves yield and quality of forage sorghum (Sorghum bicolor L.) - Muhammad Asif; Muhammad Adnan; Muhammad Ehsan Safdar; Naeem Akhtar; Ahlam Khalofah; Fahad Mohammed Alzuaibr (Journal of King Saud University: Science, 2022)
Background and objectives: Sorghum (Sorghum bicolor L.) is an important summer fodder all over the world. Phosphorus (P) is an important macronutrient which plays significant role in the growth and development of crop plants. The P is deficit in most of the Pakistani soils. Bio-stimulants are organic compounds that could enhance vegetative growth, development, nutrients’ uptake and tolerance of the plants to abiotic stresses. Methods: This two-years field experiment determined the effect of different P levels and growth stimulant (actibion) on yield and quality of forage sorghum. The P levels were 0, 30, 60 and 90 kg ha−1 and bio-stimulant (1250 ml ha−1) was applied at 20, 30 and 40 days after sowing (DAS), while distilled water was sprayed as control. Results: The results revealed that the highest values for plant height (241.70 and 237.03 cm), stem diameter (1.59 and 1.41 cm), number of leaves per plant (15.4 and 14.80), leaf area per plant (3016.8 and 2575.3 cm2), chlorophyll contents (46.17 and 44.34), fresh forage yield (47.83 and 45.33 ton ha−1) and dry matter yield (13.84 and 13.02 ton ha−1) were recorded with 60 kg ha−1 P and bio-stimulant application at 30 DAS. The similar trend was observed for crude protein (9.53 and 13.01 %). Total ash contents, plant P contents (0.17 % and 0.16 %) were improved when 90 kg ha−1 P was applied along with bio-stimulant application at 30 DAS. However, no application of P and bio-stimulant resulted in the highest values of NDF and ADF. Conclusion: It is concluded that 60 kg ha−1 P application along with foliar application of bio-stimulant at 30 DAS is optimum for improving yield and quality components of forage sorghum.